2021
DOI: 10.33448/rsd-v10i2.12711
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade do milho associado a inoculação com Azospirillum brasilense e diferentes doses de adubação nitrogenada

Abstract: Embora a adubação química nitrogenada seja responsável pelo aumento da produtividade da cultura do milho, sua aplicação também e responsável pelo aumento do custo de produção e por promover uma serie de riscos ambientais. Uma alternativa para esse problema e a fixação biológica de nitrogênio. Este trabalho tem como objetivo a avalição da eficiência da inoculação com Azospirillum brasilense na cultura do milho associada a diferentes doses de adubação nitrogenada em cobertura. O experimento foi realizado na área… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
2
Order By: Relevance
“…On the other hand, several authors found that inoculation with A. brasilense did not influence maize yield and had little influence on morphophysiological traits (Pandolfo et al, 2015;Zambonin et al, 2019) or productivity (Mumbach et al, 2017;Silva Jr;Freitas;Rezende, 2021) parameters. In accordance with these studies, our results showed that the main factor related to productivity was the soil cultivation practices, not the presence or absence of inoculation.…”
Section: Effect Of a Brasilense On Corn Yieldmentioning
confidence: 99%
“…On the other hand, several authors found that inoculation with A. brasilense did not influence maize yield and had little influence on morphophysiological traits (Pandolfo et al, 2015;Zambonin et al, 2019) or productivity (Mumbach et al, 2017;Silva Jr;Freitas;Rezende, 2021) parameters. In accordance with these studies, our results showed that the main factor related to productivity was the soil cultivation practices, not the presence or absence of inoculation.…”
Section: Effect Of a Brasilense On Corn Yieldmentioning
confidence: 99%
“…A resposta agronômica da cultura milho em associação à Azospirillum brasilense pode ser verificada em diversos trabalho (Araújo et al, 2014;Andrade et al, 2016;Moreno et al, 2019;Oliveira & Picazevicz, 2021;Silva Junior et al, 2021), com resultados promissores a respeito. Esta bactéria não tem sido tão utilizada na cultura do milho, isso pode ser atribuído a inconsistência de resultados de pesquisa, que pode variar de acordo com as condições climáticas, metodologia de condução da pesquisa e ou até mesmo o genótipo utilizado.…”
Section: Introductionunclassified
“…These bacteria can promote plant growth through physiological changes due to the release of hormones such as auxins and cytokinins that promote increased root growth (Zafar et al, 2012;Hungary et al, 2013). This genus of bacteria has been extensively studied in grass crops (Vendruscolo et al, 2018;Alvarez et al, 2019;Contardi et al, 2020;Silva Junior et al, 2021) with few results for legumes. In soybean crop (Zuffo et al, 2016) and bean cultivars conducted in the winter season (Gitti et al, 2012), no effects on grain yield were observed, although Schossler et al (2016) have obtained an increase in plant height and number of pods per common bean plant.…”
Section: Introductionmentioning
confidence: 99%